Automatic Dwelling Segmentation of Buenos Aires Province for the 2010 Argentinian Census - Bonomo, Flavia (2013)
In planning for a population census, determining which dwellings within a census tract each enumerator must visit is a logistical challenge. This challenge, which we call the dwelling segmentation problem, generally includes a set of constraints on the enumerators’ assigned routes and various criteria regarding the homogeneity and uniformity of the segmentation solutions. In this paper, we present a computational approach to solve this problem. We successfully applied our solution, which is a substantial improvement over manual methods, to the Province of Buenos Aires in the 2010 Argentinian census.